The next civil war : dispatches from the American future - Marche, Stephen (Avid Reader Press, 2022)
"On a small two-lane bridge in a rural county that loathes the federal government, the US Army uses lethal force to end a stand-off with hard-right militias, or anti-government patriots. Inside an ordinary diner, a disaffected young man with a handgun takes aim at the American president stepping in for impromptu photo-op, and a bullet splits the hyper-partisan country into violently opposed mourners and revelers. In New York City, a category 2 hurricane plunges entire neighborhoods underwater and creates millions of refugees overnight, a blow that comes on the heels of a devastating financial crash and years of catastrophic droughts, and tips America over the edge into ruin. These nightmarish scenarios are just three of the five possibilities most likely to spark devastating chaos in the United States that are brought to life here. Drawing upon sophisticated predictive models and nearly two hundred interviews with experts, military leaders, law enforcement officials, agricultural specialists, environmentalists, war historians, and political scientists, journalist Stephen Marche predicts the terrifying future collapse that so many of us do not want to see unfolding in front of our eyes. Marche has spoken with soldiers and counter-insurgency experts about what it would take to control the population of the United States, and the battle plans for the next civil war have already been drawn up. And not by novelists. By colonels"--Book jacket flap.